A General Concept on the Technical Preparation of Athletes and its Psychological Characteristics (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article describes the improvement of the technical process, the reception of information by the athlete and its development, and the effective execution of the movement.